ISU KONTEMPORER AQIDAH AKHLAK: ETIKA DIGITAL, HEDONISME, DAN MORALITAS GENERASI Z DALAM PERSPEKTIF PENDIDIKAN ISLAM - Yeni Marlina; Eka Putra Wirman; Hasnah (As-Sulthan Journal of Education, 2026)
The development of digital technology and cultural globalization have brought fundamental changes to the mindset, behavior, and value systems of young Muslims, particularly Generation Z. These changes have given rise to various contemporary issues in the areas of faith and morality, including weak digital ethics, the strengthening of a culture of hedonism, and moral degradation. This article aims to analyze in-depth contemporary issues of faith and morality related to digital ethics, hedonism, and the morality of Generation Z, and to formulate Islamic educational solutions relevant to the current context. This research uses a qualitative method with a library research approach through analysis of classic and contemporary books, scientific journals, and relevant documents in the fields of faith and morality and Islamic education. The results indicate that weak internalization of faith and moral values is a major factor in the emergence of moral deviations in the digital era. Therefore, strengthening monotheism, cultivating noble morals, Islamic digital ethics education, and synergy between families, schools, and communities are strategic solutions in shaping the character of Generation Z to be faithful, moral, and wise in utilizing technology.The abstracts submitted to As-Sulthan Journal Of Education should be clear, concise, and descriptive, using English and Indonesian, which consists of 150-200 words. The abstract contains the scope of the study, objectives, methods, research results, and conclusions. This section is separate from articles, using single space, Book Antiqua 10,  single space.